Antibacterial Activity of Boehmite Nanoparticles Synthesized by Arc Discharge in Deionized Water Technique - Rashed, Halah H (Al-Nahrain Journal of Science, 2017)
In this work, boehmite AlO(OH) nanoparticles were synthesized by arc discharge technique. The structural, surface morphology and optical properties were characterized by X-Ray Diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), Atomic Force Microscope (AFM) and Ultraviolet-Visible-Near In far Red spectrophotometer respectively. XRD results show pure orthorhombic crystalline structure of gamma-AlO(OH). FTIR absorption spectrum shows that the boehmite nps have the octahedron region which extends from (400–800 cm-1) corresponding to the vibrational frequencies of Al–O bonding. The AFM shows that boehmite NPs are spherical in shape and the average diameter is around 89 nm. Finally the optical properties results show that the boehmite nps have absorption peak at 210 nm and an optical band gap of 4.1 eV. Boehmite nps was examined susceptibility to effect on the different types of bacteria, Escherichia coli (Gram-negative) and Staphylococcus aurous (Gram-positive) strains bacteria. Boehmite NPs showed excellent antibacterial activity against two types of bacteria. Also, Staphylococcus aurous exhibited the highest sensitivity to boehmite NPs while Escherichia coli were the least sensitive.